Influence of NPK and Bokashi on Growth and Chlorophyll Content of Pakcoy (Brassica rapa L.) - Safitri, Ila; Mertha, I Gde; Raksun, Ahmad (Jurnal Biologi Tropis, 2025)
This study aimed to evaluate the effects of NPK fertilizer and bokashi on the vegetative growth and chlorophyll content of pakcoy (Brassica rapa L.). The objective was to determine both the single and interactive effects of these fertilizers on various growth parameters. The experiment was conducted at the Greenhouse of the Faculty of Agriculture, University of Mataram, from May to July 2025, using a completely randomized design (CRD) with two factors. The treatments consisted of five levels of NPK fertilizer (0–2 g/100 ml water) and five levels of bokashi (0–400 g/polybag). Data were analyzed using two-way ANOVA and Duncan’s Multiple Range Test (DMRT) at a 5% significance level. Results showed that NPK fertilizer significantly affected all growth parameters and chlorophyll content, while bokashi significantly influenced plant height, fresh weight, and dry weight. The interaction between NPK and bokashi significantly affected plant height and biomass but not leaf number, leaf area, or chlorophyll content. The best growth was obtained with 1.5 g NPK/100 ml water combined with 300 g bokashi/polybag. In conclusion, integrating organic and inorganic fertilizers improves nutrient efficiency and pakcoy productivity. These findings recommend integrated fertilization practices to promote sustainable crop production.